1999
DOI: 10.1021/jp990928h
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Electrochemical Reduction of Nitrite at an Electrochemically Roughened Silver Surface

Abstract: Photoelectrochemical reduction of nitrite and nitrate was studied on the surface of an electrochemically roughened silver electrode. The dependence of the photocurrent on photon energy, applied potential, and concentration of nitrite was determined. It was concluded that the photoelectrochemical reduction proceeds via a photoemission process followed by the capture of hydrated electrons by electron acceptors. The excitation of plasmon resonances in nanosize metal structures produced during the roughening proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 28 publications
4
37
0
1
Order By: Relevance
“…These optical and chemical responses are altered on the base of a combination of nanoparticle or nanoparticle-substrate properties that undergo either nanoparticle charging or charge transfer in plasmon-enhanced photocatalytic reactions. Cell illumination leads to several deviations from conventional cyclic voltammetry characteristic traces, such as discrete shifts in onset potential for half reactions and an increase in the photocurrent, which provide useful information on the energy barriers for the reaction [101]. This is consistent with the quantized size dependence of light-to-heat energy transformation through a Pt thin film with a thickness of several nanometers [102].…”
Section: Plasmonic Photocatalytic Electrochemical Measurementssupporting
confidence: 64%
“…These optical and chemical responses are altered on the base of a combination of nanoparticle or nanoparticle-substrate properties that undergo either nanoparticle charging or charge transfer in plasmon-enhanced photocatalytic reactions. Cell illumination leads to several deviations from conventional cyclic voltammetry characteristic traces, such as discrete shifts in onset potential for half reactions and an increase in the photocurrent, which provide useful information on the energy barriers for the reaction [101]. This is consistent with the quantized size dependence of light-to-heat energy transformation through a Pt thin film with a thickness of several nanometers [102].…”
Section: Plasmonic Photocatalytic Electrochemical Measurementssupporting
confidence: 64%
“…In these studies, a higher current density was observed for Ag (110) as compared to Ag (111) and Ag (100) [14]. Several electrocatalysts including Ag bulk [15], immobilized Ag [16], Ag-nanoparticles [17], roughened Ag surface [18], bimetallic alloy Ag/Au [19], Ag/TiO2 [20] and Ag/graphene [21] have also been reported for CO2 reduction, with CO and H2 as the main products. CO is generally adsorbs weakly on Ag and is hardly detected by vibrational spectroscopy [22].…”
Section: Introductionmentioning
confidence: 91%
“…Nitrite has been important from the viewpoint of electrochemistry because it is oxidized to nitrate and reduced to nitric oxide or other compounds. The electrodes for nitrite reduction have been reported, which contain metals [1][2][3][4][5][6][7][8][9][10], binary metals [11,12], metal complexes or metal oxides , doped diamond [34], and biological materials [35]. Some of these reports contain the reduction of both nitrate and nitrite [4][5][6][7][8][9][10][11][12][26][27][28][29][30][31][32][33][34][35], which indicates that the electrodes having a reduction activity for nitrate is effective for nitrite reduction.…”
Section: Introductionmentioning
confidence: 99%